2005
DOI: 10.1373/clinchem.2005.053363
|View full text |Cite
|
Sign up to set email alerts
|

Increased Osteoclast Activity in the Presence of Increased Homocysteine Concentrations

Abstract: Background: Increased plasma homocysteine (HCY) may be an independent risk factor for osteoporotic fractures and therefore may also adversely affect bone metabolism. We analyzed the effect of HCY on human osteoclast (OC) activity. OCs were identified as large, multinucleated cells with tartrate-resistant acid phosphatase (TRAP) activity and surface vitronectin receptors. We quantified OC activity by measuring TRAP activity. We analyzed cathepsin K (CP-K) activity in 9 donor samples and estimated the dentine-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(62 citation statements)
references
References 41 publications
1
59
0
2
Order By: Relevance
“…This conclusion is supported by cell culture experiments with human osteoclasts showing a dose-dependent increase in osteoclast activity with increasing Hcy concentrations in the culture medium (33).…”
Section: Discussionmentioning
confidence: 70%
“…This conclusion is supported by cell culture experiments with human osteoclasts showing a dose-dependent increase in osteoclast activity with increasing Hcy concentrations in the culture medium (33).…”
Section: Discussionmentioning
confidence: 70%
“…(17,28,29) In experimental settings, Hcy has been reported to affect both osteoclasts and osteoblasts. (10,11) High Hcy levels may inhibit collagen cross-linking. (6,7) The most evident correlation between Hcy and a bone marker was noted for S-CTX.…”
Section: Figmentioning
confidence: 99%
“…(1,8,9) Experimental data suggest that high Hcy levels affect both osteoclasts and osteoblasts. (10,11) If a high Hcy level is the cause of an increased fracture risk or simply a bystander is not known. (12,13) A high Hcy level could also be caused by poor nutrition, which could affect fracture risk.…”
mentioning
confidence: 99%
“…Treatment with vitamin B12 and folate, which lower Hcy levels, has been found to markedly decrease the risk of hip fracture in stroke patients (Sato et al, 2005), indicating that Hcy may play an important role in the development of osteoporosis. Although the precise mechanisms of Hcy-induced osteoporosis has not been determined, interfering with collagen cross-linking (Lubec et al, 1996), increased osteoclastic bone resorption (Herrmann et al, 2005) and decreased osteoblastic bone formation (Kim et al, 2006), have been reported to contribute to the development of Hcy-induced osteoporosis.…”
Section: Introductionmentioning
confidence: 99%